The Role of T Lymphocytes in Skeletal Muscle Repair From Traumatic and Contraction-Induced Injury - Deyhle, Michael R.; Hyldahl, Robert D. (Frontiers in Physiology, 2018)
Skeletal muscle is prone to damage from a range of stimuli, and initiates a robust repair process that requires the participation of immune cells. Among the more well characterized immune cells involved in muscle repair are those of the myeloid lineage, including neutrophils, macrophages, monocytes, and eosinophils. More recently, studies have begun to elucidate the role of the lymphoid-derived immune cells, most notably T lymphocytes (T-cells), in the complex processes of muscle repair. Though T-cells have been traditionally been associated with pathological degeneration of skeletal muscle in disease, recent studies show that T-cells are instrumental in the repair/regeneration process following severe muscle damage in mice. Furthermore, a few studies using basic immunohistochemical assays have shown that T-cells accumulate in human skeletal muscle in the days following contraction-induced muscle damage. The functional significance of T-cells in the repair and adaptation process following contraction-induce muscle damage remains uncertain, and is an active area of intense investigation. This mini-review summarizes recent findings on the involvement of T-cells in skeletal muscle repair.